A new species of Hemipteroseius (Acari: Otopheidomenidae) parasitic on Dysdercus (Hemiptera: Pyrrhocoridae) in India - Menon, Pratibha; Joshi, Sushila; Hussain, Mohammad; Ramamurthy, V. V. (Zootaxa, 2011)
A new species of ectoparasitic mite, Hemipteroseius vikrami n. sp. (Mesostigmata: Otopheidomenidae), collected on Dysdercus koenigii (Fabricius) in New Delhi and D. cingulatus (Fabricius) in Varanasi, India is described. It is distinguished from other species of the genus in having the dorsal shield divided, podonotal shield with nine pairs and opisthonotal shield with four pairs of setae; setae j6, s6 and Z5 with bulbose/spatulate tips; tritosternum with two short slightly barbed lacinae; venter with four pairs of sternal setae, one pair on the sternal shield and three pairs placed posterolaterally; anus terminal; one pair of preanal setae; movable digit of chelicera with two teeth distally; macrosetae on genu I–IV and femur I–II with bulbose/spatulate tip. A list of species of Otopheidomenidae with details of distribution and hosts, key to species of Hemipteroseius and comparison of morphological characters of species are also provided.